2012
DOI: 10.1136/bjophthalmol-2012-301612
|View full text |Cite
|
Sign up to set email alerts
|

Foveal avascular zone and foveal pit formation after preterm birth

Abstract: Preterm birth results in abnormal foveal vascularisation, a failure of the inner retinal neurons to migrate away from the fovea, and an elevated outer nuclear layer ratio. The spatial coincidence of inner retinal and vascular abnormalities in preterm children supports the hypothesis that aspects of foveal development are interdependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
92
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 35 publications
13
92
1
2
Order By: Relevance
“…In addition, the study speculated that the retention of the inner retina might contribute to the abnormal foveal morphology in patients with a history of ROP. Several studies have reported a thick fovea in premature children and have associated it with early GA and/or low BW [5, 7, 8]. Similarly, our study demonstrated that the eyes in the ROP group had the greatest foveal thickness of all groups.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, the study speculated that the retention of the inner retina might contribute to the abnormal foveal morphology in patients with a history of ROP. Several studies have reported a thick fovea in premature children and have associated it with early GA and/or low BW [5, 7, 8]. Similarly, our study demonstrated that the eyes in the ROP group had the greatest foveal thickness of all groups.…”
Section: Discussionsupporting
confidence: 71%
“…Our layer analysis of retinal SS-OCT images confirmed thicker central IRL and ONL+ layers in preterm children, as we and others have previously described [6, 30-32]. Significantly reduced BCVA showed a high correlation with a disproportion of the ONL+ and the IRL ( R = 0.824).…”
Section: Discussionsupporting
confidence: 63%
“…[1][2][3][4][12][13][14] Electroretinography also suggests that central retinal dysfunction is greater than peripheral dysfunction. 5 OCT has revealed changes not evident on ophthalmoscopy, but these can be compatible with good visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown shallowing of the foveal depression, thickening of the central macula, and a continuity of inner retinal layers across the fovea in those born severely preterm, often despite normal macular appearance on ophthalmoscopy. [6][7][8][9][10][11][12][13][14] However, these macular changes evident on OCT are still compatible with good visual acuity. 6,7,[9][10][11] This has prompted authors to suggest that other factors might be contributory to the variation in vision seen in these patients.…”
Section: Introductionmentioning
confidence: 95%